Selected renal cells harbor nephrogenic potential - Narayan, Prakash; Bruce, Andrew T.; Rivera, Elias A.; Bertram, Timothy A.; Jain, Deepak (Frontiers in Medicine, 2022)
Selected renal cells (SRC), a renal epithelial cell-enriched platform, is being advanced as autologous cell-based therapy for treatment of chronic kidney disease. However, the mechanism underlying its renal reparative and restorative effects remains to be fully elucidated. In this study we coupled data from knowledgebases with empirical findings to demonstrate that genes differentially expressed by SRC form interactomes within tubules and glomeruli and mediate a suite of renal developmental activities including epithelial cell differentiation, renal vasculature development, and glomerular and nephron development. In culture SRC forms organoids which self-assemble into tubules in the presence of a scaffold. Implanted into kidneys of subtotally nephrectomized rat, SRC is associated with comma- and S-shaped body cell formation and glomerular development, and improvement in serum creatinine and renal microarchitecture. These data suggest that SRC harbors nephrogenic potential which may explain, at least in part, its therapeutic activity.